Phase investigation of a cobalt base alloy containing Cr, Ni, W and C - Kuzucu, V; Ceylan, M; Celik, H; Aksoy, I (Elsevier Science Sa, 1998)
A cobalt base alloy with composition Co-27.74Cr-19.27Ni-6.11W-1.1C was cast, some pieces of this alloy being cooled in water and liquid nitrogen after annealing. Metallographic investigations showed that the cast sample had a dendritic microstructure with eutectic carbides solidified in the inter-dendritic regions. In the samples cooled in water and liquid nitrogen, the carbide phases solidified in the inter-dendritic regions in the cast sample dispersed in the dendritic grains, as a result of this dispersion, the dendritic grains becoming smaller and the branches of dendrites becoming thinner. In accordance with these metallographic observations, the hardness measurements showed that the hardness of the samples cooled in water and liquid nitrogen increased according to the cast sample. It was seen from the X-ray diffraction investigations that various carbides such as M7C3, M23C6, M3C2, Co3C, Ni3C, and sigma phase may exist in these samples. In addition, DSC (Differential Scanning Calorimetry) measurements showed that some recovery processes occur in these samples in the heating regime in the temperature region between 238 and 287 degrees C. (C) 1998 Elsevier Science S.A.
Keywords: cobalt-base alloy; phase investigation; X-ray diffraction